Factors Contributing to The Failure of SMMEs in the Mining Construction Sector in the Northern Cape - Pretorius, S.; Carls, L. (The South African Journal of Industrial Engineering, 2025)
Small, medium, and micro enterprises (SMMEs) play an important role in economic development, employment, and poverty reduction in South Africa. However, SMMEs in the mining construction sector have very high failure rates, particularly in regions such as the Northern Cape, where the mining sector is a prime pillar of the economy. This study investigates the failure of SMMEs, using a case study methodology. It focuses on key factors that could influence the management of these SMMEs. Four propositions are presented, all of which were validated by the findings. Interviews were conducted with 12 SMME owners, and secondary data were obtained from the SMMEs and other external sources. This study aims to contribute to the limited literature on the factors that influence the success of SMMEs in the mining construction sector in developing countries.